Laser Physics - Pashenin, Pavel P.; SpringerLink (Online service) (Moscow : MAIK Nauka/Interperiodica : Imprint: MAIK Nauka/Interperiodica.)
From 2013 Laser Physics will no longer be distributed by Springer.
Keywords: Lasers; Photonics; Optics, Lasers, Photonics, Optical Devices